A fully packed spheroidal hybrid generator for water wave energy harvesting and self-powered position tracking. (March 2020) - Chandrasekhar, Arunkumar; Vivekananthan, Venkateswaran; Kim, Sang-Jae
Abstract: Water waves are a promising source of renewable energy. Their kinetic energy can potentially drive energy harvesters. Herein, we describe a fully packed spheroidal smart buoy hybrid generator (SB-HG) composed of triboelectric nanogenerator (TENG) and an electromagnetic generator (EMG) for scavenging water-wave energy. Each of the energy harvesting components generated electrical outputs from the same wave motion. A position-tracking long-range (LoRa) device placed in the buoy enabled identification of the buoy location when it was placed in the sea for energy harvesting, navigation, and fishnet tracking purposes. A solar cell placed on the top of the buoy powered the device under calm wave conditions. The TENG and EMG components generated maximum electrical outputs of 100 V/2 μA and 20 V/15 mA, respectively. Combining the devices efficiently converted the kinetic energy of the waves into useful electrical energy, which was used to charge a commercial capacitor and lithium-ion battery. The charged battery drove the position-tracking LoRa device for a positioning application and demonstrated that the SB-HG device is an inexpensive and reliable candidate for ocean navigation systems. Our water-wave energy harvester is highly promising as a clean energy power source and as a self-powered sensor for various environmental monitoring systems. Graphical abstract: Image 1 Highlights: A smart buoy hybrid generator is made of TENG-EMG omponents which can be driven by water waves. The electrical output of the device is greatly enhanced due to the hybrid configuration. The device is made as a scalable and multi-unit device for the enhanced energy harvesting capability in a single device. The device is used as a self-powered position tracking by using a LoRa module and interface with mobile phone application.